Limestone as material to reduce sulphate and arsenic content in acid mine drainage - Sulaiman, Azli (2015)
In this paper, limestone was used to reduce sulphate and arsenic content in acid mine drainage (AMD). The sample of acid mine drainage was collected from tailing tin mine pond located in Perak. The sulphate content in acid mine drainage was analysed before and after treatment with limestone by using DR 2800 spectrophotometer. ICP-OES was used to analyse water sample before and after treatment for arsenic content analysis. pH multi parameter was used to determine pH value, oxidation reduction potential and electrical conductivity (EC) of water sample before and after treatment. Limestone used was collected from a quarry in Simpang Pulai, Ipoh. The size of limestone used was less than 2 mm. The experiment was carried out by using experimental column. After treatment with limestone the result showed that the pH value increased from 2.4 to 6.5, whilst sulphate and arsenic content decreased. The best parameter was 500 g limestone with 75 minutes retention time.